Optoelectronics of solar cells - Smestad, Greg P. (SPIE, 2002)
With concerns about worldwide environmental security, global warming, and climate change due to emissions of carbon dioxide from the burning of fossil fuels, it is desirable to have a wide range of energy technologies in a nation's portfolio. Photovoltaics, or solar cells, are a viable option as a nonpolluting renewable energy source. This text is designed to be an overview of photovoltaic solar cells for those in the fields of optics and optical engineering, as well as those who are interested in energy policy, economics, and the requirements for efficient photo-to-electric energy conversion.
"SPIE digital library."
Keywords: Solar cells.; Optics.; elektronické knihy; electronic books